Legal Foundations of Corporate Law in The Republic of Uzbekistan - Tillabaev Durbek Rustamovich (Penerbit Jurnal Indonesia, 2024)
This article discusses the legal basis of corporate law in the Republic of Uzbekistan. An analysis of key legal acts, such as the Civil Code, the Law “On Joint-Stock Companies and Protection of Shareholders’ Rights” and the Law “On Business Companies” was carried out. Particular attention is paid to the structure of corporate governance bodies, the rights and responsibilities of shareholders, as well as mechanisms for protecting their rights. The role of regulatory bodies, the influence of international standards and best practices on the development of corporate governance in Uzbekistan are explored. In conclusion, proposals are presented to improve legal norms and strengthen mechanisms for protecting the rights of shareholders.